2016
DOI: 10.3892/ol.2016.4340
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib and etoposide combinations exert synergistic effects on the human prostate cancer cell line PC-3

Abstract: Abstract. Novel treatment modalities are urgently required for androgen-independent prostate cancer. In order to develop an alternative treatment for prostate cancer, the cytotoxic effects of the 26S proteasome inhibitor bortezomib, either alone or in combination with the two commonly used chemotherapeutic agents irinotecan and etoposide, on the human prostate cancer cell line PC-3 were evaluated in the present study. The PC-3 cell line was maintained in Dulbecco's modified Eagle's medium with 10% fetal bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The effect of metuzumab, gemcitabine or the metuzumab/gemcitabine combination on cell viability were assessed by MTT assay as described previously. 39,40 Briefly, 5 × 10 3 NSCLC cells (A549, NCI-H460 and NCI-H520) were seeded in 96-well plate and cultured in 24 h, metuzumab, gemcitabine, the metuzumab/gemcitabine combination and saline were added to the cells. After additional 24h of respective treatments, 20 μL of MTT (5 mg/ml) was added into the wells and cells were incubated for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of metuzumab, gemcitabine or the metuzumab/gemcitabine combination on cell viability were assessed by MTT assay as described previously. 39,40 Briefly, 5 × 10 3 NSCLC cells (A549, NCI-H460 and NCI-H520) were seeded in 96-well plate and cultured in 24 h, metuzumab, gemcitabine, the metuzumab/gemcitabine combination and saline were added to the cells. After additional 24h of respective treatments, 20 μL of MTT (5 mg/ml) was added into the wells and cells were incubated for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Our final gene, PSMD12, has not been previously implicated in prostate cancer, but dysregulation of the proteasome has been associated with prostate cancer. Inhibition of the proteasome with therapeutics like bortezomib has been shown to increase the efficacy of first generation anti-androgens like bicalutamide by decreasing the expression of AR and AR-V [41] or induce sensitivity of AR-independent prostate cancer cells to etoposide [42]. Unfortunately, proteasome inhibitors, to date, have proven acutely toxic, and targeting PSMD12 with currently available therapeutics is unlikely to provide a favorable risk-to-benefit ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Large proteolytic complexes of proteasome are normally labeled with Ubiquitin which systematically destroys more than 80 % of regulatory proteins associated with regulation of cell cycle, cell death and differentiation by spontaneously increasing the accumulation of pro-apoptotic proteins and decreasing the activity and degradation of NF-kB (14,15). Studies have revealed that selective proteasome inhibitors induce cell death by making them susceptible to chemotherapeutic agents in the breast (16), prostate (17), pancreatic (18), and ovarian cancers (19). In 2012, Carfi lzomib (an epoxomycin derivative) has been approved by the Food and Drug Administration (FDA) as the second generation proteasome inhibitor for the treatment of multiple myeloma, showing lower toxicity than the classic proteasome inhibitors (20).…”
Section: Introductionmentioning
confidence: 99%